Pediatric Neurology Workforce in Saudi Arabia - Al-Nahdi, Bayan M.; Ashgar, Mowadah W.; Domyati, Mayasem Y.; AlWadei, Ali H.; Albaradie, Raidah S.; Jan, Mohammed M. (Journal of Pediatric Neurology, 2017)
Background The availability of pediatric neurologists remains a global problem. Strategic planning and tackling issues related to optimizing the care of children with neurologic disorders depend on the workforce, which we aim to evaluate in this study.Method Physicians practicing in the field of pediatric neurology in Saudi Arabia were identified from the database of national societies. A structured 30-item online survey was designed to examine their clinical practice, experience, and availability of supporting services.Results A total of 56 pediatric neurologists completed the survey, mostly (48%) practicing in the capital city of Riyadh. Many of them worked alone (30%) or with only one other colleague (21%). Based on their responses, the estimated total number of pediatric neurologists across the country was 75 with a ratio of 1.06 pediatric neurologists per 100,000 children < 15 years of age. They had very busy services with 66% evaluating > 15 patients per clinic and 79% reporting difficulties in finishing on time. The majority (87.5%) felt overwhelmed, which correlated with working alone (p = 0.002), having no assistant consultant (p = 0.039), and having no access to international sent-out laboratories (p = 0.02). The majority (94.5%) needed additional help in dealing with the volume and complexity of their patients, which correlated with feeling overwhelmed (p = 0.006).Conclusion Although the total number of pediatric neurologists across Saudi Arabia has improved significantly over the last decade, their distribution remains uneven leading to shortages in many regions. This adds to the excessive workload and affects the quality of the provided services.
Keywords: pediatric neurology; workforce; practice; Saudi Arabia